The Design and Fabrication of Manhole Cleaning Machine Using Glass Fiber Gripper - S. Nitish Kumar; SK. John Gopi; U. Pavan Kumar; N. Naga Manikanta; E. Madhu Sruthi (International Journal of Engineering and Management Research, 2023)
Manual scavenging is one of the major problems facing by the whole world. Particularly manhole cleaning is getting more dangerous and harmful to workers involving in the cleaning process. According to research 50% of the sewer workers die before the age of 50 due to health issues. In order to reduce and stop this problem the design and fabrication of manhole cleaning machine is presented in this project as a solution. The new manhole cleaning machine is used to clean the manhole without involving the worker to go inside the manhole. The machine uses mechanical gripper made up of glass fiber. It uses screw mechanism to collect and dispense the sludge. The gripper is carried by a vehicle which will travel on the track. The track and vehicle make the system to be continuous and automatic. The track can accommodate multiple grippers for continuous removal of sludge. Dc motors are used as the major power transferring devices.